Blockchain Assisted Gamified Learning and Augmented Reality Driven NextGen e-Learning Ecosystem for STEM Education - Sinha, Rita; Sarma, Bhairab; Borah, Dhruba Jyoti (INFOCOMP Journal of Computer Science, 2025)
The high pace rise in e-Learning demands has revitalized academia-industries to achieve scalable EdTech solution. Despite numerous digital solutions, the complex nature of science, technologies, engineering, and mathematics (STEM) education makes most of the state-of-art method limited. STEM education requires e-Learning model to be more interactive, socializing, engaging and cognitive to inculcate self-realization. Gamified learning and augmented reality techniques serves as an e-Learning mechanism; however, there is no potential framework employing these approaches to fulfill STEM learning demands. Considering it as motivation, in this paper a robust Blockchain Assisted Gamified Learning and Augmented Reality Driven NextGen Ecosystem for STEM e-Learning is proposed. The key components of the proposed conceptual e-Learning framework are the blockchain smart contract, decentralized data storage, subject-specific content READ (read, edit, add, delete) functions, personalized display, Quick Check, Prompt Check, Reality Corner, etc. Considering the need of the secure decentralized e-Learning framework the proposed framework employs blockchain smart-contract provision that enables seamless multi-party data access and computation. Distributed data storage is proposed to provide decentralized access to the students and teachers to improve system scalability and availability. Virtual Reality section provides content adaptive augmented reality solutions, demonstration etc., which can be contributed by both teachers as well as students. The conceptualized model is designed in such way that it motivates STEM students to engage more, socialize and enjoy the platform to yield superior outcomes. It can improve their self-realization, cognitive behave, problem solving ability and consistent amongst the students. Moreover, it can be vital for teachers as well as it can make overall teaching more flexible and productive.